2019
DOI: 10.1371/journal.pone.0219468
|View full text |Cite
|
Sign up to set email alerts
|

Association between emotional intelligence and academic success among undergraduates: A cross-sectional study in KUST, Pakistan

Abstract: The study investigated the association between emotional intelligence and academic success among undergraduates of Kohat University of Science & Technology (KUST), Pakistan. A sample of 186 students who were enrolled during the semester Fall 2015 to Spring 2018 was selected through a random sampling technique. A cross-sectional, descriptive and correlational research methods were employed in this study. A standardized tool “Emotional Intelligence Scale” was employed for the collection of information from the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 27 publications
6
72
1
5
Order By: Relevance
“…During university life students enhance their abilities and capabilities along with their academic achievement. In Pakistan many studies were conducted on the relationship between emotional intelligence and academic achievement such as Adnan, Chaudhry and Malik (2012) on students of management sciences; similarly Suleman, Hussain, Syed, Parveen, Lodhi, & Mahmood, (2019) conducted study on science and technical students, Kayani, Kayani, & Saleem (2015) conducted similar students on postgraduate level students of Public Sector Universities of Rawalpindi Pakistan; Malik, & Shahid, (2016) conducted a similar study on business students but no study was available on undergraduate students. So, it is needed to study the levels of emotional intelligence of students to help them in achieving personal distinction in the subjects they are studying.…”
Section: Studies On Emotional Intelligence and Academic Achievementmentioning
confidence: 99%
“…During university life students enhance their abilities and capabilities along with their academic achievement. In Pakistan many studies were conducted on the relationship between emotional intelligence and academic achievement such as Adnan, Chaudhry and Malik (2012) on students of management sciences; similarly Suleman, Hussain, Syed, Parveen, Lodhi, & Mahmood, (2019) conducted study on science and technical students, Kayani, Kayani, & Saleem (2015) conducted similar students on postgraduate level students of Public Sector Universities of Rawalpindi Pakistan; Malik, & Shahid, (2016) conducted a similar study on business students but no study was available on undergraduate students. So, it is needed to study the levels of emotional intelligence of students to help them in achieving personal distinction in the subjects they are studying.…”
Section: Studies On Emotional Intelligence and Academic Achievementmentioning
confidence: 99%
“…However, other studies reported strong positive relationship between EI and academic success among undergraduate students. [ 25 ] The mean perceived stress score was significantly lower in the excellent group than the average group. Foster et al .…”
Section: Discussionmentioning
confidence: 98%
“…The results revealed that students with a higher level of emotional intelligence achieved better academic results. In addition, academic success was strongly associated with the managing relations, integrity, and self-development dimensions, and moderately associated with self-awareness, empathy, self-motivation, emotional stability, value orientation, commitment, and altruistic behaviour [ 44 ]. McCann et al’s meta-analysis concluded that emotional intelligence is a predictive factor for academic success, especially in humanities-related areas of knowledge.…”
Section: Discussionmentioning
confidence: 99%